Synthesis, Metabolism, and Signaling Mechanisms of Hydrogen Sulfide: An Overview - Bełtowski, Jerzy (Methods in molecular biology (Clifton, N.J.), 2019)
In addition to nitric oxide (NO) and carbon monoxide (CO), hydrogen sulfide (H S) has recently emerged as the novel gasotransmitter involved in the regulation of the nervous system, cardiovascular functions, inflammatory response, gastrointestinal system, and renal function. H S is synthesized from L-cysteine and/or L-homocysteine by cystathionine β-synthase, cystathionine γ-lyase, and cysteine aminotransferase together with 3-mercaptopyruvate sulfurtransferase. In addition, H S is enzymatically metabolized in mitochondria by sulfide:quinone oxidoreductase, persulfide dioxygenase, and sulfite oxidase to thiosulfate, sulfite, and sulfate which enables to regulate its level by factors such as oxygen pressure, mitochondria density, or efficacy of mitochondrial electron transport. H S modifies protein structure and function through the so-called sulfuration or persulfidation, that is, conversion of cysteine thiol (-SH) to persulfide (-SSH) groups. This, as well as other signaling mechanisms, is partially mediated by more oxidized H S-derived species, polysulfides (H S ). In addition, H S is able to react with reactive oxygen and nitrogen species to form other signaling molecules such as thionitrous acid (HSNO), nitrosopersulfide (SSNO ), and nitroxyl (HNO). All H S-synthesizing enzymes are expressed in the vascular wall, and H S has been demonstrated to regulate vascular tone, endothelial barrier permeability, angiogenesis, vascular smooth muscle cell proliferation and apoptosis, and inflammatory reaction. H S-modifying therapies are promising approach for diseases such as arterial hypertension, diabetic angiopathy, and atherosclerosis.